Detection of IgE‐reactive proteins in hydrolysed dog foods. Issue 6 (2nd August 2017) - Roitel, Olivier; Bonnard, Lionel; Stella, Alexandre; Schiltz, Odile; Maurice, Delphine; Douchin, Gaël; Jacquenet, Sandrine; Favrot, Claude; Bihain, Bernard E.; Couturier, Nicolas
Abstract : Background: Commercial hydrolysed diets are used for the diagnosis of food allergy in dogs. The cleaved parent proteins are presumed to be too small to elicit an allergic response by reacting with allergen‐specific immunoglobin E (IgE). Objectives: To evaluate three commercial hydrolysed dog diets for proteins. Animals: Sera were collected from dogs with suspected food allergy. Methods: Two batches of each hydrolysed diet were examined by electrophoresis and visualized by Coomassie blue, silver nitrate staining and IgE immunoblotting. Results: From two to five proteins, ranging from 21 to 67 kDa, were detected in all three diets evaluated. Circulating IgE antibodies targeting these proteins were detected by immunoblotting of dog sera. Six different carbohydrate proteins were identified by mass spectrometry; maize/potato granule‐bound starch synthase‐1, soybean glycinin, soybean β‐conglycinin α chain, potato aspartic protease inhibitor, rice glutelin type B1 and soybean sucrose‐binding protein. Four of these proteins have been described as allergens in humans. Conclusions: Some commercial hydrolysed diets contain carbohydrate proteins. Some dogs have circulating IgE antibodies targeting these proteins. The clinical significance of these findings is unknown. Abstract : Background – Commercial hydrolysed diets are used for the diagnosis of food allergy in dogs. The cleaved parent proteins are presumed to be too small to elicit an allergic response by reacting with allergen‐specific immunoglobin E (IgE).Objectives – To evaluate three commercial hydrolysed dog diets for proteins.Conclusions – Some commercial hydrolysed diets contain carbohydrate proteins. Some dogs have circulating IgE antibodies targeting these proteins. The clinical significance of these findings is unknown.